Peran Biaya Peluang dalam Pengambilan Keputusan Usaha Mahasiswa Politeknik Negeri Medan - Natasya Amelya; Raihana Syahira; Rico Natanael Hagana Bangun (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study focuses on analyzing students' business decisions at Medan State Polytechnic, considering the role of opportunity costs. The approach used is a descriptive quantitative method, with 32 active students taken as samples through purposive sampling. The researcher used a questionnaire with a Likert scale of 1-5 for Opportunity Cost (X) and Student Business Decision (Y) respectively. The Opportunity Cost obtained an average of 3.85 and Business Decision 4.01, which are in the high category. This indicates that students are rational and thorough in their business decisions. This supports students' understanding of opportunity costs and student business decision making, which suggests that opportunity costs have a positive influence.